Stochastic Extinction in an SIRS Epidemic Model Incorporating Media Coverage. (12th December 2013) - Wang, Liyan; Huang, Huilin; Xu, Ancha; Wang, Weiming
Abstract : We extend the classical SIRS epidemic model incorporating media coverage from a deterministic framework to a stochastic differential equation (SDE) and focus on how environmental fluctuations of the contact coefficient affect the extinction of the disease. We give the conditions of existence of unique positive solution and the stochastic extinction of the SDE model and discuss the exponential p -stability and global stability of the SDE model. One of the most interesting findings is that if the intensity of noise is large, then the disease is prone to extinction, which can provide us with some useful control strategies to regulate disease dynamics.